Virulence genes in isolates ofKlebsiella pneumoniaefrom the UK during 2016, including among carbapenemase gene‐positive hypervirulent K1‐ST23 and 'non‐hypervirulent' types ST147, ST15 and ST383. Issue 1 (January 2018) - Turton, Jane F.; Payne, Zoë; Coward, Amy; Hopkins, Katie L.; Turton, Jack A.; Doumith, Michel; Woodford, Neil
Abstract : Purpose. : Klebsiella pneumoniae is a concern because of its multidrug resistance and the ability of hypervirulent types, especially capsular type K1‐clonal complex 23 (K1‐CC23), to cause community‐acquired, life‐threatening infections. Hypervirulent types carry an array of virulence genes including rmpA / rmpA2, coding for capsule up‐regulation. We sought to identify isolates carrying these elements among submissions to the UK national reference laboratory during 2016. Methodology. : Virulence elements and carbapenemase genes were sought by PCR or from whole genome sequences. Isolates were typed by variable number tandem repeat analysis or by multi locus sequence typing from whole genome sequences. Long read nanopore sequencing was carried out on two isolates. Results/Key findings. : Twelve of 1090 isolates (1.1 %) belonged to hypervirulent K1‐CC23, with one carrying bla OXA‐48 (KpvST23L_OXA‐48). A further 24 rmpA / rmpA2 ‐positive isolates were detected: eight belonged to hypervirulent types of capsular types K2 and K54; and 14 belonged to 'non‐hypervirulent' ST147, ST15 and ST383 and also carried carbapenemase gene(s). Virulence, heavy metal and antibiotic resistance gene contents were compared from whole genome sequences of KpvST23L_OXA‐48 and one of the ST147 isolates carrying bla NDM‐1 . They carried 94/96 and 26/96 of the virulence genes sought, and 23/23 and 9/23 of the heavy metal resistance genes, respectively. In the ST147 isolate, rmpA / rmpA2 and the aerobactin siderophore cluster were on a large virulence plasmid together with resistance genes. The yersiniabactin cluster was widely present among carbapenemase gene‐positive isolates, including among those that were rmpA / rmpA2 ‐negative. Conclusion. : Our results highlight a combination of virulence and resistance genes, which could lead to untreatable invasive infections.